First Fossil Fokienia (Cupressaceae) in South China and Its Palaeogeographic and Palaeoecological Implications - Wu, Xinkai; Zhang, Hao; Kodrul, Tatiana M.; Maslova, Natalia P.; Jiang, Songyao; Yin, Qianyi; Quan, Cheng; Jin, Jianhua (Frontiers in Earth Science, 2021)
Fokienia A. Henry & H. H. Thomas is a monotypic genus of the Cupressoideae Pilger (Cupressaceae), native to subtropical evergreen mesophytic forests in South China, northern Laos and Vietnam. The fossil record of Fokienia is very scanty, with only one known occurrence of foliage in the Oligocene of Longjing, Jilin, China. Here we report the fossil foliage of Fokienia discovered in the Miocene Erzitang Formation of the Guiping Basin, South China, which is similar to that of the only extant species Fokienia hodginsii in both macromorphological and epidermal features. This species is the earliest fossil record within the modern distribution area of Fokienia and the only fossil species for which morphology and anatomy have been studied in detail. Fossil evidence suggests that the genus Fokienia was present at middle latitudes of the Northern Hemisphere in the Oligocene and spread to South China during the Miocene. Due to physiological adaptations to warm-wet environments and weak cold tolerance, Fokienia migrated southward, as global climate cooling gradually drove it to extinction in the mid-latitudes. The ecological niche of the extant species, and co-existing plant fossils, suggest that the fossil assemblage represents the remains of an evergreen broad-leaved and conifer mixed forest growing under humid and warm Miocene climate.